A Review of Gene Editing/Therapy and CRISPR Technology - Khing S. Ong; Zack S.T. Lim; Boenjamin Setiawan (Cermin Dunia Kedokteran, 2019)
This review will discuss the gene editing or manipulation in general, including various methods and tools currently available, including CRISPR. Some encouraging results of clinical applications of gene-therapy will also be discussed. With its diverse and far reaching effect on biomedical field, we will also discuss CRISPR technology beyond its gene-editing functions. We also review the cost for performing a gene-therapy. Ulasan ini membahas penyuntingan atau manipulasi gen umumnya, berbagai cara dan alat yang kini tersedia, termasuk teknologi CRISPR. Akan disajikan pula hasil-hasil percobaan klinik yang memberi harapan. Mengingat pengaruhnya yang luas di bidang biomedis, akan dibahas pula pemanfaatannya di bidang lain. Akhirnya, akan dibicarakan juga hal-hal terkait biaya pengeditan terapi gen yang sangat tinggi, dengan harapan bisa ditekan di masa yang akan datang dengan teknologi yang lebih canggih.